2017
DOI: 10.3892/ol.2017.5817
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between ultrasound-guided fine needle aspiration cytology of axillary lymph nodes and sentinel lymph node histopathology in early-stage breast cancer

Abstract: Abstract. The replacement of sentinel lymph node biopsy (SNB) by ultrasound-guided fine-needle aspiration (US-guided FNA) cytology of axillary lymph nodes is controversial, despite the simplicity and reduced cost of the latter. In the present study, US-guided FNA was performed in 27 patients with early-stage breast cancer for comparison with SNB. Data were analyzed by calculation of sample proportions. Tumor subtypes included invasive ductal carcinoma (85%), invasive lobular carcinoma (7%), and tubular and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…However, considering the definite operative histology as a reference, the second-look AUS and FNAB revealed false-negative results in 30.7% and 52.2% of our cases, respectively. Hence, AUS-guided FNAB was associated a PPV of 96.12% but an NPV of 47.83%, supporting the previously reported low NPV (ranged 59.3% to 73.0%) and high false negativity (ranged 19.4% to 31.8%) of this method in detecting ALN metastases [ 10 , 11 , 13 , 17 , 20 , 27 , 28 ]. Given that the negative AUS-FNAB revealed nonmetastatic axillae only in half of our patients, our findings seem to support that AUS-FNAB alone is not likely to be relied upon in axillary investigation to replace SLNB for the time being due to moderate sensitivity and the high false-negative rate [ 17 , 20 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…However, considering the definite operative histology as a reference, the second-look AUS and FNAB revealed false-negative results in 30.7% and 52.2% of our cases, respectively. Hence, AUS-guided FNAB was associated a PPV of 96.12% but an NPV of 47.83%, supporting the previously reported low NPV (ranged 59.3% to 73.0%) and high false negativity (ranged 19.4% to 31.8%) of this method in detecting ALN metastases [ 10 , 11 , 13 , 17 , 20 , 27 , 28 ]. Given that the negative AUS-FNAB revealed nonmetastatic axillae only in half of our patients, our findings seem to support that AUS-FNAB alone is not likely to be relied upon in axillary investigation to replace SLNB for the time being due to moderate sensitivity and the high false-negative rate [ 17 , 20 ].…”
Section: Discussionsupporting
confidence: 83%
“…Notably, in a past study with 27 early-stage breast cancer patients, FNAB in comparison with SLNB was reported to have a sensitivity, specificity, PPV and NPV of 45%, 100%, 100%, and 73%, respectively [ 13 ]. The authors concluded the similar specificity of FNAB-based and SLNB-based ALN cytology in the presence of ALN metastases, whereas lower sensitivity of FNAB than SLNB when lymph node cytology is negative, indicating that negative AUS-FNAB results do not rule out the metastatic implants [ 13 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current clinical practice, conventional US-guided FNAB is a common method to diagnose ALN before surgery [29]. However, the moderate sensitivity of conventional US may lead to a relatively high FNR [30,31]. A previous study has shown that the sensitivity and FNR of US-guided FNAB for detecting metastatic ALNs in early breast cancer were 45% and 55%, respectively [32].…”
Section: Discussionmentioning
confidence: 99%
“…This increases the likelihood of a positive FNAC considerably and explains some of the higher reported sensitivity rates, and might explain our sensitivity rate since we performed FNAC regardless of suspicion of metastasis on US examination. Nonetheless, low sensitivity and moderate negative predictive values remain an issue [ 25 ].…”
Section: Discussionmentioning
confidence: 99%